World masterpieces (New York : Norton, 1956)
Contents.-- v.1. Literature of Western culture through the Renaissance. -- v.2. Literature of the Western culture since the Renaissance
Includes indices.
Keywords: Literature -- Collections; English literature -- Collections from foreign literature